Web Technologies and Applications 16th Asia-Pacific Web Conference, APWeb 2014, Changsha, China, September 5-7, 2014. Proceedings - Chen, Lei.; Jia, Yan.; Sellis, Timos; Liu, Guanfeng; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 16th Asia-Pacific Conference APWeb 2014 held in Changsha, China, in September 2014. The 34 full papers and 23 short papers presented were carefully reviewed and selected from 134 submissions. The papers address research, development and advanced applications of large-scale data management, web and search technologies, and information processing.
Large-scale data management -- Web and search technologies -- Information processing.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval; Multimedia information systems; Computer Science; Data Mining and Knowledge Discovery; Information Storage and Retrieval; Database Management; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Electronic books